2010
DOI: 10.1111/j.1755-3768.2009.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and menopausal status on peripheral and choroidal circulation

Abstract: ABSTRACT.Purpose: To evaluate the influence of menopausal status and age on peripheral and ocular circulation assessed by means of continuous laser Doppler flowmetry (LDF). Methods: Fifty-three healthy participants were recruited randomly. Twenty-six men and 27 women were divided into two age groups. Choroidal blood flow was measured by LDF and peripheral circulation was measured at the fingertips (digit IV) using the Perimed PeriFlux (Ja¨rfa¨lla, Sweden) laser Doppler System 5000. Independent t-test and two-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
1
27
1
1
Order By: Relevance
“…However, the even distribution of these medications over the three groups would suggest a similar impact on the retrobulbar arteries that were studied. Additionally, our population presented with a high MOPP when compared for other reports assessing ocular blood flow (Resch et al 2011) (Kavroulaki et al 2010). This increased perfusion pressure must be taken into account when comparing conclusions as it may influence the arteries resistance and diameter at the time of study.…”
Section: Discussionmentioning
confidence: 65%
“…However, the even distribution of these medications over the three groups would suggest a similar impact on the retrobulbar arteries that were studied. Additionally, our population presented with a high MOPP when compared for other reports assessing ocular blood flow (Resch et al 2011) (Kavroulaki et al 2010). This increased perfusion pressure must be taken into account when comparing conclusions as it may influence the arteries resistance and diameter at the time of study.…”
Section: Discussionmentioning
confidence: 65%
“…Difference in hormonal exposure is a likely biological explanation. One study reported estrogen receptor in human choroid, and it has been indicated that sex and hormonal status may influence choroidal blood flow [23][24][25]. Ulaş et al [26] reported that CT decreased significantly in the mid-luteal phase of the menstrual cycle in young healthy women.…”
Section: Discussionmentioning
confidence: 97%
“…4,17 The significance of this finding remains uncertain; it has been suggested that one biological explanation may be a different hormonal exposure between males and females. Indeed, sex and hormonal status influence the choroidal blood flow, 21,22 and, therefore, also may influence the choroidal volume. However, as Park et al have reported recently, the effect of hormones may not be significant, at least in children.…”
Section: Discussionmentioning
confidence: 99%